Enhanced friction and shock sensitivities of hexachlorodisilane hydrolyzed deposit mixed with KOH. (July 2021) - Nguyen, Thanh-Trung; Lin, Yu-Jhen; Lin, Zhi-Xuan; Tai, Hui-Chu; Tsai, Hsiao-Yun; Chen, Jenq-Renn; Ngai, Eugene Y.
Abstract: In this work, the effects of potassium hydroxide (KOH) on friction and shock sensitivity of the hexachlorodisialne hydrolysis products were studied. A wide range of KOH content, from 0.02 to 21.5 wt%, in the mixture of KOH and HCDS hydrolyzed deposit was prepared by mixing the deposit with aqueous KOH solution and dried in glovebox. The lowest impact energy (LIE) and lowest friction force (LFF) were determined by BAM fall-hammer and friction test apparatus, respectively. It was found that both shock and friction sensitivities increased with an increase in the KOH content in the HCDS hydrolyzed deposit. In particular, the LIE and LFF decrease from 6 J to 326 N of the original deposit to less than 0.125 J and 7 N for deposit with 0.03 and 0.3 wt% KOH. Differential scanning calorimetry studies showed that a new exothermic peak was observed between 80 °C and 150 °C which is also accompanied by evolution of hydrogen. It is proposed that, the presence of KOH results in the formation of Si–Si–OK groups leading to the weakening of the neighboring Si–Si bonds. Any mechanical impact or friction will lead to the cleavage of the unstable Si–Si bonds and subsequently initiate a fast chain oxidation of adjacent Si–Si and Si–OH bonds to form more Si–O–Si groups, releasing H2 gas and heat. Recommendations were given for handling and disposing of these explosive deposits. Highlights: KOH treated HCDS hydrolyzed deposit is extremely sensitive to impact and friction. Structure of KOH treated HCDS hydrolyzed deposit is characterized. A mechanism of increased sensitivities is proposed. Recommendations are given for safe handling these deposits.